INOVASI PENGEMBNAGAN KURIKULUM PAI BERBASIS KURIKULUM TERINTEGRASI DI PONDOK PESANTREN DAAR EL QOLAM - Nuruliana, Chandra; fauzi, ahmad fauzi; Sirojudin, Rumbang; Helnanelis (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2025)
Islamic boarding school is the oldest Islamic educational institution in Indonesia, possessing a distinct intellectual tradition, local culture, and unique educational system. Despite undergoing various changes due to modernization, the pesantren maintains its Islamic identity through an independent educational model, rooted in tradition, yet adaptive to the demands of the times. The evolution of the educational system has given rise to two types of pesantren: Salaf pesantren that focus on the study of classical texts, and Khalaf (modern) pesantren that integrate religious and general sciences using classical teaching methods and foreign language instruction. This transformation requires pesantren to continuously conduct curriculum development that is relevant, effective, and capable of addressing global challenges, including resource limitations, national regulatory demands, and the needs of modern society. Pondok Pesantren Daar El Qolam, as one modern pesantren, implements an integrated curriculum that combines the national curriculum, the Gontor curriculum, and the institution's specific curriculum. However, its implementation faces challenges such as mastery of Arabic and English, and the heterogeneity of new students' academic backgrounds. Therefore, curriculum development in pesantren requires a comprehensive approach that involves all stakeholders to achieve the goals of Islamic education, namely forming individuals who are faithful, knowledgeable, virtuous, and capable of adapting to changing times.